Quantitative analysis of weak current rectification in molecular tunnel junctions subject to mechanical deformation reveals two different rectification mechanisms for oligophenylene thiols versus alkane thiols - Xie, Zuoti; Bâldea, Ioan; Nguyen, Quyen Van; Frisbie, C. Daniel (Nanoscale, 2021)
Metal-molecule-metal junctions based on alkane thiol (CnT) and oligophenylene thiol (OPTn) self-assembled monolayers (SAMs) and Au electrodes are expected to exhibit similar electrical asymmetry, as both junctions have one chemisorbed Au-S contact and one physisorbed, van der Waals contact. Asymmetry is quantified by the current rectification ratio RR apparent in the current-voltage (I-V) characteristics. Here we show that RR < 1 for CnT and RR > 1 for OPTn junctions, in contrast to expectation, and further, that RR behaves very differently for CnT and OPTn junctions under mechanical extension using the conducting probe atomic force microscopy (CP-AFM) testbed. The analysis presented in this paper, which leverages results from the previously validated single level model and ab initio quantum chemical calculations, allows us to explain the puzzling experimental findings for CnT and OPTn in terms of different current rectification mechanisms. Specifically, in CnT-based junctions the Stark effect creates the HOMO level shifting necessary for rectification, while for OPTn junctions the level shift arises from position-dependent coupling of the HOMO wavefunction with the junction electrostatic potential profile. On the basis of these mechanisms, our quantum chemical calculations allow quantitative description of the impact of mechanical deformation on the measured current rectification. Additionally, our analysis, matched to experiment, facilitates direct estimation of the impact of intramolecular electrostatic screening on the junction potential profile. Overall, our examination of current rectification in benchmark molecular tunnel junctions illuminates key physical mechanisms at play in single step tunneling through molecules, and demonstrates the quantitative agreement that can be obtained between experiment and theory in these systems.
Gesehen am 18.11.2021